Recent progress in MOCVD growth for thermoelectrically cooled HgCdTe medium wavelength infrared photodetectors. (April 2016) - Gawron, W.; Martyniuk, P.; Kębłowski, A.; Kolwas, K.; Stępień, D.; Piotrowski, J.; Madejczyk, P.; Pędzińska, M.; Rogalski, A.
Highlights: We presented the mid-wave HgCdTe MOCVD growth procedure on GaAs substrate with CdTe buffer layer. Hg/Te and Cd/Te mole ratios were provided for mid-wave HgCdTe growth procedure. Temperature profile of the growth process was provided. Hillocks were not observed in areas over 60 × 60 μm 2 . TAT mechanism was suppressed at the N + -absorber interface – the MWIR detectors made of the grown epi-layers. Abstract: The authors report on advanced metalorganic chemical vapour deposition (MOCVD) of Hg1− x Cd x Te (HgCdTe) structures for high operating temperature, medium wavelength infrared (MWIR) detector application. MOCVD technology with wide range of composition and donor/acceptor doping and without post grown annealing was proved to be an excellent tool for HgCdTe heterostructure epitaxial growth used for uncooled photodetector design. The interdiffused multilayer process (IMP) technique was applied for the HgCdTe deposition. HgCdTe epilayers were grown at 350 °C with Hg source kept at 210 °C. The II/VI mole ratio was assumed in the range from 1.5 to 3 during CdTe/HgTe cycles of the IMP process. The MWIR detectors grown by MOCVD exhibit detectivity ∼7.3 × 10 11  Jones at λPEAK   = 3.5 μm and T  = 230 K being determined by background limited photodetector (BLIP) condition.